Mergers and Acquisitions from the Perspective of Competitive Advantage: the Perdigão Agroindustrial S.A. - Oliveira, Oderlene Vieira de (2007)
The organizations interested in new segments of the market can choose strategies of fusion and acquisition. The success of these transactions is normally measured be the expectation of return of the invested capital. This article, however, pondered the results from a manager’s point of view. We understand by result any tangible or intangible effect on the organizational environment and the company’s position facing the market. Thus, we have attempted to answer the following question: did the acquisition of Batavo Frios generate competitive advantage to Perdigão Agroindustrial S.A.? Searching for an answer to the problem, the study has aimed at checking if the process of acquisition has brought competitive advantage while focusing on two phases (i) integration and (ii) acquisition management (assimilation). The case was investigated in 16 branches through interviews (face-to-face and on the telephone), and secondary material. The gathering of data took place in 2006 and 2007. The study was of exploratory nature with a qualitative approach. To the consolidation of data the content analysis technique, especially the theme analysis has proven most appropriate. We can conclude that the acquisition of Batavo Frios has generated relative competitive advantage to Perdigão Agroindustrial S.A.Key-words: Fusions and acquisitions. Competitive Advantage. Resources.